The Habit of “Let's Write Cheerfully” for Children Aged 5-6 Years Old - Monitasari, Aprillia; Katoningsih, Sri (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2021)
Aim This research is early childhood as someone who is just starting the stage of development in the world with various experiences that children get. Children have their own weaknesses and strengths where the weaknesses and strengths of the child need to be considered and then developed according to their talents. This research can be a source to motivate children aged 5-6 years to like writing as a way of preparing themselves to enter school to the next level. Method is research articles from several